Implementation of quantum gates using decision diagrams. (October 2021) - de Souza, Renan Rodrigues; Piqueira, José Roberto C.
Abstract: This article proposes a set of algorithms to compress the representation of quantum states and emulate their evolution when modeling gates representing quantum information processes. The employed methodology is based on detailed descriptions of the data structures that represent the states. Procedural languages have been applied to reduce the computational costs of the memory access processes. A modification of the binary trees is used as the framework for the entire development. The required memory and processing time are considerably reduced when this approach is applied when implementing quantum gates and algorithms. Graphical abstract: Highlights: Algorithms to compress representation of quantum states and their evolution are proposed. Using procedural languages and binary trees, quantum gates are implemented reducing memory and processing time. Complexity is dropped from exponential to polynomial in the presented examples of quantum gates and algorithms. Quantum decision diagrams (QDD) strategy to implement quantum processes is three times faster than the classical Grover's strategy.